Bahasa IndonesiaSTRATEGI PEMASARAN DIGITAL KONTEN MUSIK EDUKATIF ANAK USIA DINI DI KANAL KINDERFLIX - Dini Ardiningsih; Muhammad Sandy Saputra (Jurnal Sekretaris dan Administrasi Bisnis, 2025)
Music-based educational content has increasingly become a preferred approach in supporting the development of early childhood learners. Kinderflix, a YouTube channel that focuses on children’s music content, implements a well-structured digital strategy to reach its target audience while consistently maintaining educational value in each of its videos. This study explores how the channel build its appeal through consistent visual presentation, the selection of pedagogically strong characters, and the production of original song as a key differentiator. The research adopts a qualitative descriptive approach, with data collected through direct observation of the channel. Review of relevant literature, and semi-structured interviews with the channel’s co-founder. The findings reveal that the use of specific keywords, strategic uploading scheduling, and active engagement with parent are integral components of a comprehensive and consistently applied marketing strategy. Of the 196 songs produced, the majority are original compositions, which not only strengthen the channel’s identity but also create opportunities for commercialization through derivative products. These finding suggest that an approach combining creative content development, digital algorithm literacy, and strong educational orientation can contribute to the creation of a relevant and sustainable learning ecosystem in the digital era.